KINERJA OPERATOR OPERATOR DITINJAU DARI KOMPETENSI, LINGKUNGAN KERJA, ETOS KERJA DAN LOYALITAS PADA SMP DI KABUPATEN SUKOHARJO - Sudi Winasis; Sudarwati; Sarsono (ITB AAS Indonesia Surakarta, 2025)
The purpose of this study is to determine the partial and simultaneous influence of competence, work environment, work ethic, and loyalty on the performance of school operators at junior high schools throughout Sukoharjo Regency. The research was conducted at the Department of Education and Culture of Sukoharjo Regency. This type of research is correlational in nature, which aims to explain asymmetric relationships between the variables studied. The sample consisted of 79 school operators working at junior high schools across Sukoharjo Regency. Data were collected through questionnaires, interviews, observations, and documentation. Data analysis techniques included multiple regression tests, F-tests, t-tests, and the coefficient of determination (R²) test. The results showed that competence, work environment, work ethic, and loyalty have both partial and simultaneous effects on the performance of school operators at junior high schools in Sukoharjo Regency. Using the SPSS program, the R² value was found to be 0.888 or 88.8%, indicating that the independent variables—Competence (X1), Work Environment (X2), Work Ethic (X3), and Loyalty (X4)—together influence the Performance of School Operators (Y) in Sukoharjo Regency by 88.8%. The remaining 11.2% is influenced by other factors not examined in this study, such as incentives, facilities and infrastructure, rewards, and others. Keywords: Competence, Work Environment, Work Ethic, Loyalty, Performance